Pengaruh Profesionalisme Auditor, Komitmen Organisasi dan Etika Profesi Pada Kinerja Auditor Kantor Akuntan Publik Provinsi Bali - Gita Wulandari, Anak Agung Sayu; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p11, 2018)
In the current era of globalization there are so many legal cases involving accounting manipulation. The auditor's profession has been a public spotlight in recent years. An auditor must have a high professionalism in carrying out his duties. Audit results from an auditor should be accountable to the parties concerned. The performance of the auditor is the result of the auditor's work in performing the assignment of examination of the financial statements of an entity with the aim of determining the reasonableness of the financial statements. The purpose of this study is to determine the influence of auditor professionalism, organizational commitment, and professional ethics on the performance of auditors public accounting firm in Bali Province. Sampling method used is purposive sampling method, while data collection method is done by using questioner. The population in this study are all auditors who work at Public Accounting Firm in Bali Province. Public Accounting Firm used is Public Accounting Firm which is registered in the Directory published by Indonesian Institute of Certified Public of 2017 which is located in Bali a number of 7 Public Accounting Firm. The total number of auditors from 7 offices is 65 auditors. The number of research samples used were 36 respondents. Data analysis technique used is multiple linear regression analysis technique. The results of this study indicate that auditor professionalism, organizational commitment, and professional ethics have a positive effect on auditor performance. Keywords: Auditor Professionalism, Organizational Commitment and Professional Ethics, Auditor Performance